Pool boiling heat transfer of saturated water on rough surfaces with the effect of roughening techniques - Fan, Simiao (2021)
The effect of surface roughness on pool boiling heat transfer was experimentally investigated in the saturated water. Eight testing surfaces were fabricated on plain copper through three preparation methods including random polishing, unidirectional polishing, and femtosecond laser machining. The surface roughness in the present study is characterized by the areal (three dimensional, 3D) roughness parameter. In the two dimensional (2D) profile roughness analysis, we know that a profile can be separated into the large-scale component (waviness) and the short-scale component (roughness). The arithmetical mean height of the profile, the waviness and the roughness are denoted as Pa, Wa, and Ra, respectively. However, there are no such kind of parameters defined in the 3D roughness analysis. To distinguish them, we define Sap and Sa in this study, corresponding to Pa and Ra in the 2D roughness parameters. The pool boiling experiments show that a rougher surface has higher heat transfer coefficient than a smoother one only within the same surface preparation method, if the surface roughness is characterized by Sap. For the surfaces prepared by the different techniques, the laser processed rough surface with Sap=3.40 µm could have deteriorated heat transfer coefficient compared with the relatively smooth one polished by the 180 grit sandpaper with Sap=1.29µm. However, the different trend is observed when the surface roughness is characterized by Sa. By applying a standardized filtration process, the large-scale component of the surface can be removed, and the areal arithmetical mean height calculated from the remaining part is denoted as Sa. The boiling curves are found to shift monotonically to the left as Sa becomes larger, regardless of the surface preparation methods. The enhancement in heat transfer coefficient of rougher surfaces is attributed to a combined result of larger nucleation sites, smaller departure bubbles and higher bubble departure frequencies, according to the visualization study. On the other hand, the critical heat flux (CHF) does not show a clear trend with the surface roughness when the different surface preparation methods are involved, no matter Sap or Sa is used. The measurements of static contact angle infer that the CHF is not only dependent on surface roughness, but also highly related to surface wettability. A correlation is developed to well predict the heat transfer coefficient from the experiments as a function of Sa, especially in the fully developed nucleate boiling region.